The rebranding process implementation of an independent hotel into a hotel chain - Ribeiro, Mariana de Oliveira Castanhas Casal (2018)
Nowadays the number of hotels that feel the need to change their brands is increasingly a reality present in the hotel industry. Based on this industry characteristic, the present thesis aims to study the implementation process of rebranding an independent hotel into a hotel chain through the case study of Sheraton Cascais Resort. Supported by a review of the existing literature on this topic, the case study presents a real analysis in terms of implementing the rebranding process in hospitality. The methodology of analysis concentrates a deductive method of direct observation where all data collected derives from the accomplishment of a 6-month internship within the property and from interviews conducted to the hotel General Manager and Human Resources Director. The study is limited to the component directly visible to the guest, due to the existence of strict brand privacy and confidentiality policies that do not allow analyzing or making public information regarding the internal component of service. All the research conducted throughout the case study allowed recognizing that the correct implementation of rebranding follows all four and sequential phases proposed by the Ahonen´s (2008) model. Future studies should be carried out allowing following the hotel at a stage before, during and after rebranding, in order to investigate the rebranding outcome with greater accuracy